Analysis of volatiles from feces of released Przewalski’s horse (Equus przewalskii) in Gasterophilus pecorum (Diptera: Gasterophilidae) spawning habitat - Ran Zhou (Nature Portfolio, 2021)
Abstract The absolute dominant species that infests wild population of Przewalski’s horse (Equus przewalskii) is Gasterophilus pecorum, and feces of released Przewalski’s horse, a habitat odor, plays an important role in mating and ovipositing locations of G. pecorum. To screen out unique volatiles for attracting G. pecorum, volatiles from fresh feces of released horses at stages of pre-oviposition (PREO), oviposition (OVIP), and post-oviposition (POSO) of G. pecorum, and feces with three different freshness states (i.e., Fresh, Semi-fresh, and Dry) at OVIP were collected by dynamic headspace adsorption and determined by automatic thermal desorption GC–MS. Results show that there were significant differences in fecal volatiles within both test conditions. Of the five most abundant volatiles from the five individual samples, the most important volatile was ammonium acetate at OVIP/Fresh, followed by acetophenone (Semi-fresh), toluene (PREO, OVIP and POSO), butanoic acid (OVIP and Semi-fresh), acetic acid (PREO, POSO and Semi-fresh), 1,6-octadiene,3,7-dimethyl-,(S)- (PREO, OVIP and POSO), 1,5,9-undecatriene,2,6,10-trimethyl-,(Z)- (PREO and Semi-fresh) and caprolactam (all conditions), which seem to be critical substances in oviposition process of G. pecorum. The findings may be beneficial to development of G. pecorum attractants, facilitating prevention and control of infection by G. pecorum to released Przewalski’s horse.